Emerging links between cerebrovascular and neurodegenerative diseases—a special role for pericytes. (16th October 2019) - Lendahl, Urban; Nilsson, Per; Betsholtz, Christer
Abstract: Neurodegenerative and cerebrovascular diseases cause considerable human suffering, and therapy options for these two disease categories are limited or non‐existing. It is an emerging notion that neurodegenerative and cerebrovascular diseases are linked in several ways, and in this review, we discuss the current status regarding vascular dysregulation in neurodegenerative disease, and conversely, how cerebrovascular diseases are associated with central nervous system (CNS) degeneration and dysfunction. The emerging links between neurodegenerative and cerebrovascular diseases are reviewed with a particular focus on pericytes—important cells that ensheath the endothelium in the microvasculature and which are pivotal for blood–brain barrier function and cerebral blood flow. Finally, we address how novel molecular and cellular insights into pericytes and other vascular cell types may open new avenues for diagnosis and therapy development for these important diseases. Abstract : This review focuses on how pericytes link cerebrovascular and neurodegenerative diseases, and how recent insight into pericyte function might potentially be used for therapy.